First-Order Phase Transition in a Modified Ziff-Gulari-Barshad Model with Self-oscillating Reactant Coverages - Sinha I.; Mukherjee A.K. (My University, 2025)
Using kinetic Monte Carlo simulations, we study the effect of oscillatory kinetics due to surface reconstructions on Ziff-Gulari-Barshad (ZGB) model discontinuous phase transition. To investigate the transition, we do extensive finite size scaling analysis. It is found that the discontinuous transition still exists. On inclusion of desorption in the model, the order-parameter probability distribution broadens but remains bimodal. That is, the first-order phase transition becomes weaker with increase in desorption rate. © 2012 Springer Science+Business Media, LLC.